Hadoop the definitive guide - White, Tom (O'Reilly, 2010)
Counsels programmers and administrators for big and small organizations on how to work with lascale application datasets using Apache Hadoop, discussing its capacity for storing and processing large amounts of data while demonstrating best practices for building reliable and scalable distributed systems.
Includes bibliographical references and index. - Print version record
Keywords: Apache Hadoop (Computer file); File organization (Computer science); Fichiers (Informatique); Organisation; Data processing; Databases